A rare case of multicentric eosinophilic granulocytic sarcoma as cause of hindlimb weakness and non‐regenerative anaemia in a minipig. Issue 3 (29th June 2021) - Weyrich, Angelika; Becker, Sabrina; Vienenkötter, Julia; Reiner, Gerald; Herden, Christiane
Abstract: A 6‐year‐old male, neutered minipig developed progressive hindlimb weakness and finally became recumbent. Clinical and laboratory examination revealed restricted hindlimb mobility and weight bearing with unimpaired reflexes and proprioception as well as marked non‐regenerative macrocytic anaemia, neutropenia and lymphocytopenia. Underlying bone marrow disease and haematopoietic neoplasia were assumed after exclusion of spinal disc herniation and infectious causes for anaemia. Despite stabilising therapy, the animal died 7 days later. Postmortem examination revealed multiple beige‐coloured nodules affecting many organs including the bone marrow and consisting of neoplastic round cells with intracytoplasmic eosinophilic granules. Using various histopathological stains and immunohistochemistry, the neoplastic cells were determined to be of eosinophil granulocyte origin. Granulocytic sarcoma is a rare form of myeloid neoplasia with only two published porcine cases. With the increasing popularity of minipigs as companion animals, extensive awareness and information concerning illnesses in these animals should be available to practitioners.